A comparative study on characteristics of composite (Cr3C2-NiCr) clad developed through diode laser and microwave energy - Hebbale A.M.; Kumar M.; Soudagar M.E.M.; Ahamad T.; Kalam M.A.; Mubarak N.M.; Alfantazi A.; Khalid M. (Nature Research, 2024)
A typical ferrite/martensitic heat-resistant steel (T91) is widely used in reheaters, superheaters and power stations. Cr3C2-NiCr-based composite coatings are known for wear-resistant coatings at elevated temperature applications. The current work compares the microstructural studies of 75 wt% Cr3C2- 25 wt% NiCr-based composite clads developed through laser and microwave energy on a T91 steel substrate. The developed clads of both processes were characterized through a field emission scanning electron microscope (FE-SEM) attached with energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and assessment of Vickers microhardness. The Cr3C2-NiCr based clads of both processes revealed better metallurgical bonding with the chosen substrate. The microstructure of the developed laser clad shows a distinctive dense solidified structure, with a rich Ni phase occupying interdendritic spaces. In the case of microwave clad, the hard chromium carbide particles consistently dispersed within the soft nickel matrix. EDS study evidenced that the cell boundaries are lined with chromium where Fe and Ni were found inside the cells. The X-ray phase analysis of both the processes evidenced the common presence of phases like chromium carbides (Cr7C3, Cr3C2, Cr23C6), Iron Nickel (FeNi3) and chromium-nickel (Cr3Ni2, CrNi), despite these phases iron carbides (Fe7C3) are observed in the developed microwave clads. The homogeneous distributions of such carbides in the developed clad structure of both processes indicated higher hardness. The typical microhardness of the laser-clad (1142 65HV) was about 22% higher than the microwave clad (940 42 HV). Using a ball-on-plate test, the study analyzed microwave and laser-clad samples' wear behavior. Laser-cladding samples showed superior wear resistance due to hard carbide elements. At the same time, microwave-clad samples experienced more surface damage and material loss due to micro-cutting, loosening, and fatigue-induced fracture. 2023, The Author(s).